Μνήμη in Herodotus II 77, 2: “History” or “Tradition”? - Narecki, Krzysztof (Polskie Towarzystwo Filologiczne, 2022)
In this short article, the author analyses the word μνήμη in one specific place in the Histories by Herodotus (II 77, 1), taking into account the broad context in which this word appears. Previous commentators and translators have perceived mneme to be broadly understood as “history”, as contained in the various documents that record extensive knowledge of the Egyptians from the region which is described by Herodotus in Book II. In contrast to this previously held view, the present author explains mneme as “tradition” recorded in time, i.e. a rich collection of customs (νόμοι, τὰ νόμαια) which cover habits, views, beliefs, behaviours and social norms cultivated (ἐπασκέοντες) by very wise people (λογιώτατοι) whom Herodotus encountered during his trip to Egypt. In such a sense, μνήμη is used here for the first time in the history of the word’s usage.